An investigation of the role of conflict in the stratificationary process of the African in the copper mining industry of Northern Rhodesia between the years, 1943-1961 - Coetzee, J A G (Rhodes University, Faculty of Humanities, Department of Sociology, 1964)
The aim of this study is to investigate the role of CONFLICT in the stratificationary process of the African in the Copper Mining Industry of Northern Rhodesia between the years 1943 - 1961. The hypothesis and assumptions which it is desired to prove can be classified as falling into four categories: 1. that which accepts human beings as individuals acting in group structures, each group having its appropriate goals and ends forming discernable patterned action systems; 2. that these groups can be reconstructed to show variable patterns of action which might be either accommodative or initially contradictory as conflicts emerge within the system; 3. that items 1 and 2 above can be objectivised by empirical materials and that they change in time, and, in so doing, are modified in structure-functional relations; 4. that conflict is the process which animates the patterns and prescribes new goals and ends within the patterned activity systems. An indefinite number of causality factors are possible in explaining social change, but we confine ourselves to the concept CONFLICT, with special reference to the Copperbelt of Northern Rhodesia. The economic factors operating, together with the political and social factors, producing a typical stratification of the African in the industry, sofar as this reveals changing patterns of progressive and aggressive goal thrusts and redefinition of the social positions of the contesting participants, are dealt with in the appropriate sections of this investigation. The model has been developed in relation to the study of the total social system with special emphasis on their overtly political and economical aspects. Part 1, in its entirety, deals with the theory of conflict. It also contains our own development of the theme. The empirical data are contained in parts 2, 3, with a section on envisaged future social developments. The conclusion, to this investigation, forms the last part , with an exhaustive testing of the TEN-POINT HYPOTHESIS given at the end of Part 1.
Keywords: Social conflict -- Zambia; Conflict management -- Zambia; Copper industry and trade -- Zambia